Strategic use of enzyme-linked immunosorbent assay as a complementary tool for the diagnosis of bovine tuberculosis - Camussone, Cecilia (2026)
Bovine tuberculosis (bTB) is a global chronic disease. Argentina's bTB eradication program consists of the Caudal-Fold Tuberculin test (CFT) and the sacrifice of positive animals as the principal measure. However, despite the implementation of the control program, CFT-positive animals continue to appear in some herds, which generates skepticism about the potential to eradicate tuberculosis. The objective of this work was to evaluate the suitability of an ELISA test for the detection of M. bovis specific antibodies (bTB-ELISA) in CFT-negative animals as a complementary strategy to control bTB. A convenience sampling of dairy farms was conducted through contact with owners, and those who agreed to the research protocol were selected. Two studies were conducted in eight (study 1) and six (study 2) dairy farms. Cows were tested by CFT, and those negative to this test were tested using ELISA in three cycles, one cycle per year during three consecutive years (study 1) and three cycles applied consecutively for 1 year (study 2). The prevalence of bTB-ELISA-positive animals showed a significant reduction towards the third sampling in both strategies. Although the general trend was towards a reduction in bTB-positive animals using CFT, this behavior was not homogeneous among dairy farms, evidencing that intra-farm factors are relevant. The repeated application of the CFT test together with ELISA was a useful strategy for the reduction of CFT-positive animals. It should be noted that this approach must be accompanied by good management practices in the herd to prevent the entry and spread of the disease.